An Evaluation Method for General Quality Process Capability of Equipment Based on Normal Cloud Model - Deng Hao, Huang Zegui, Cai Zhongyi, Wang Mengqi, Zhang Kai (Hangkong bingqi)
In view of the problems that the evaluation system for general quality characteristics fails to cover the whole life-cycle of equipment, and there is a disconnect between general quality characteristics and functional characteristics during the equipment development process, this paper presents the concept of general quality process capability. On the basis of this concept, it establishes the evaluation method for general quality process capability of equipment based on normal cloud model. Firstly, combining the development mode of the research institutes and the characters of whole life-cycle of equipment, this paper constructs 3D evaluation index system including purchasers, research institutes, and users. Then, it uses the AHP-entropy weight method, which is calculated on the subjective and objective weight deviation value ωbias, to couple weights of all indices. Finally, referring to the maturity model, the general qua-lity process capability of equipment is divided into five levels, and the fuzzy comprehensive evaluation of process capability is completed using the normal cloud model. Taking a certain equipment as a case, through comparison with different weighting method and evaluation models, the results indicate that the index system is in conformity with the practical situation, the allocation of weights is relatively scientific and reasonable. This evaluation method can reflect the index system fuzziness and randomness.